2022
DOI: 10.3389/fpubh.2022.975507
|View full text |Cite
|
Sign up to set email alerts
|

Hand washing practice among public primary school children and associated factors in Harar town, eastern Ethiopia: An institution-based cross-sectional study

Abstract: BackgroundHand washing with soap and water reduces the risk of diarrheal episode by 28–48% and acute respiratory infection by 20–50%. However, there is limited evidence on hand washing practices among students in Eastern Ethiopia, particularly in Harari town. Therefore, this study aimed to determine hand washing practice among primary school students and associated factors in Harar town, Eastern Ethiopia.MethodsAn institution-based cross-sectional study was applied among 670 students in Harar town from June 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“… 20 , 21 An institutional-based cross-sectional study that was conducted to assess handwashing practice of students in 6 public primary schools in Harar town, the capital of Harari Regional State in eastern Ethiopia, reported lower handwashing practice at critical times such as 13.3% after using the toilet and 51.3% before eating. 22 Besides, more than half of the students were washing their hands for less than 20 seconds, indicating insufficient practice. According to, 23 32% of primary school children in Sebeta town, Oromia Regional State (Ethiopia), which is adjacent to Addis Ababa City, practiced proper handwashing.…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 21 An institutional-based cross-sectional study that was conducted to assess handwashing practice of students in 6 public primary schools in Harar town, the capital of Harari Regional State in eastern Ethiopia, reported lower handwashing practice at critical times such as 13.3% after using the toilet and 51.3% before eating. 22 Besides, more than half of the students were washing their hands for less than 20 seconds, indicating insufficient practice. According to, 23 32% of primary school children in Sebeta town, Oromia Regional State (Ethiopia), which is adjacent to Addis Ababa City, practiced proper handwashing.…”
Section: Introductionmentioning
confidence: 99%
“…Children need to be taught these habits, by parents, teachers, health workers, and they need access to hand washing facilities. [8][9][10] In our study, the most common presenting symptoms were fever, anorexia and neuropsychiatric symptoms including confusion, delirium and agitation and headache. Although headache is relatively common in some paediatric studies, neuropsychiatric symptoms are rarely reported in children.…”
Section: Discussionmentioning
confidence: 56%
“…Children are at increased risk of contracting typhoid because they are less likely to wash their hands prior to eating and after using the toilet. Children need to be taught these habits, by parents, teachers, health workers, and they need access to hand washing facilities 8–10 …”
Section: Discussionmentioning
confidence: 99%
“…Hand washing is incredibly important for preventing illnesses and schools are thought to be the best location to inculcate this habit in childhood. Most students in this study (64.12%) were female, the majority of students in another study of the same sort (56.9%) were female 22 . The survey found that 69.7% of schoolchildren practiced good hand washing.…”
Section: Discussionmentioning
confidence: 57%